2013
DOI: 10.1159/000348250
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Thrombin Peptide TP508 Enhances VEGF-Stimulated Angiogenesis and Attenuates Effects of Chronic Hypoxia

Abstract: Revascularization of chronic wounds and ischemic tissue is attenuated by endothelial dysfunction and the inability of angiogenic factors to stimulate angiogenesis. We recently showed that TP508, a nonproteolytic thrombin peptide, increases perfusion and NO-dependent vasodilation in hearts with chronic ischemia and stimulates NO production by endothelial cells. In this study, we investigated systemic in vivo effects of TP508 on VEGF-stimulated angiogenesis in vitro using aortic explants in normoxic and hypoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Our previous studies showed that TP508 stimulates eNOS to produce NO (28) and reverses effects of hypoxia-induced ED to restore myocardial function (30) and prevent the loss of endothelial cell responses to VEGF (29). Because exposure to radiation has been shown to induce ED (68, 12, 13), we conducted studies to determine whether irradiation of HCAEC would affect NO production by endothelial cells in response to VEGF or TP508, which stimulate NO production by two different mechanisms (28).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies showed that TP508 stimulates eNOS to produce NO (28) and reverses effects of hypoxia-induced ED to restore myocardial function (30) and prevent the loss of endothelial cell responses to VEGF (29). Because exposure to radiation has been shown to induce ED (68, 12, 13), we conducted studies to determine whether irradiation of HCAEC would affect NO production by endothelial cells in response to VEGF or TP508, which stimulate NO production by two different mechanisms (28).…”
Section: Resultsmentioning
confidence: 99%
“…injection of TP508 stimulated aortic endothelial cell sprouting and prevented hypoxia-induced loss of endothelial function when aortic explants were removed from nonirradiated mice 24 h after injection and cultured on Matrigel ex vivo (29). Thus, we chose to use this modified aortic sprouting assay to determine whether systemic injection of TP508 could protect endothelial function in vivo after whole-body gamma irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations